Pre-service teachers’ beliefs about teaching English to older adults: The case of motivation - Agata Słowik-Krogulec (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
As of 2021, in Poland there are hardly any University courses preparing pre-service teachers to teach groups of the age of 60 and older. However, at the same time, it is estimated that in Poland older adults represent approximately 24% of the population and it is expected to increase to 40.4% by 2050. The number of private language centres and Universities of the Third Age (U3A) offering, among other subjects, foreign language education, is also constantly growing. In order to examine the value of introducing “Foreign Language Geragogy” (FLG, i.e. teaching foreign languages to older adults) to the curriculum, a qualitative study of forty two MA students from the Institute of English Studies (University of Wrocław) was carried out. Only half of the respondents attended the elective course and MA seminar “Older adults and SLA”, but both groups completed the same open-ended questionnaire, the aim of which was to explore pre-service teachers’ subjective theories regarding older adults’ motivation to learn foreign languages in later life, and to examine the extent to which they were affected by the content of the course. The results suggest that such courses are valuable, and pre-service teachers’ opinions regarding foreign language learning and teaching to older adults should be challenged in order to offer a better quality of teaching and to promote the idea of lifelong learning.